"How to match research designs to organisational issues in health and social care" - LEE, MANDY S. (Health Service Executive, 2013)
This paper provides an overview of the key considerations we need to take into account when deciding on a suitable research design for addressing particular service issues in health and social care, with emphasis on the task of identifying research questions at each stage of the applied research process. I present a model for determining research rigour in health services research and a model for defining research questions for each stage of the applied research cycle, from problem specification through to outcome assessment. The paper concludes with a check-list of the key issues we need to consider when designing a health services research project.
How to Conduct Research for Service Improvement: A Guidebook for Health and Social Care Professionals
PUBLISHED
Keywords: Research Design; Health Services Research